Optical and structural characteristics of SnO2 nanocrystalline thin film - Ali, Mohammad M. (University of Thi-Qar Journal of Science, 2011)
Nanocrystalline tin dioxide (SnO ) thin film was prepared on glass substrate by chemical vapour deposition (CVD), taking starting material tin chloride solution (SnCl 2 .2H 2 2 O). The thin film were characterized for the composition by x-ray diffraction, the XRD result shows a regular, smooth morphology. The deposited film was found to bepolycrystalline and consisted only of the tetragonal phase SnO with no structural change, and they were well crystallized during deposition. The average grain size was found to be 33.35 nm as calculated by XRD using Debye Scherror Formula. After annealing the films in air at 400, 500, and 600 o2 C the grain size was 27.905 nm, 27.263 nm, and 32.172 nm respectively. The optical properties (absorbance and transmittance) have been measured.